1994
DOI: 10.1111/j.1574-6968.1994.tb07178.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of lithotrophic ammonia-oxidizing bacteria on hydroxylamine

Abstract: Nitrosomonas europaea, Nitrosomonas nitrosa and Nitrosococcus oceanus were successfully grown on hydroxylamine. Significant cell yields were obtained in media containing ammonia supplemented with successive small additions of hydroxylamine. The molar growth yield on hydroxylamine, measured as formation of cell protein per unit of substrate oxidized, was found to be approximately twice that on ammonia. In respiration experiments, the oxygen consumption was 1.5 mol O2 per mol ammonia and 1.0 mol O2 per mol hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Additionally, N. europaea is capable of growing mixotropically on ammonia and hydroxylamine. Under anoxic conditions, hydroxylamine is oxidized with nitrite as an electron acceptor, and nitrous oxide is produced . Therefore, during alternating loadings in the absence of oxygen, AOB are likely to be activated when using hydroxylamine and ammonia as substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, N. europaea is capable of growing mixotropically on ammonia and hydroxylamine. Under anoxic conditions, hydroxylamine is oxidized with nitrite as an electron acceptor, and nitrous oxide is produced . Therefore, during alternating loadings in the absence of oxygen, AOB are likely to be activated when using hydroxylamine and ammonia as substrates.…”
Section: Discussionmentioning
confidence: 99%
“…N. europaea are capable of growing mixotropically on ammonia and hydroxylamine. In the absence of oxygen, hydroxylamine was oxidized with nitrite as electron acceptor, while nitrous oxide was produced [22,23]. Under anoxic or oxygen-limited conditions, the oxygen source is unknown.…”
Section: Denitrifying Nitrifiersmentioning
confidence: 99%
“… 13 The AOB denitrification pathway in both co- and counter-diffusion biofilms is largely stimulated by the diffusion of NH 2 OH into the anoxic region of the biofilm, where no oxygen would compete for the electrons generated by NH 2 OH oxidation with ( Figs 3 , 4 , 5 ). High N 2 O production rates in the presence of NH 2 OH and were also observed under anoxic conditions using suspended cultures 21 22 . The thicker biofilm generates higher N 2 O production is partly due to the extensive anoxic region for nitrite reduction ( Fig.…”
Section: Discussionmentioning
confidence: 73%
“…In order to fully clarify the interactions among N 2 O production, NH 2 OH and oxygen diffusion, and electron transportation by AOB in biofilms, the simulations in this work are performed based on the assumption that AOB are evenly distributed throughout the biofilm. It has been reported that AOB are able to grow on NH 2 OH oxidation and thus occupy an extended biofilm region 21 28 , while NOB are inhibited in the presence of NH 2 OH 29 30 . Nevertheless, further investigation is required to reveal the effect of diffusion geometry on N 2 O formation in more complex biofilms, where AOB, NOB, Anammox bacteria and/or heterotrophic organisms may co-exist and compete for substrates and growth space within the biofilm.…”
Section: Discussionmentioning
confidence: 99%